Epoxidised natural rubber (ENR)/polyvinyl chloride (PVC)/silica (SiO2) membrane for treating palm oil mill effluents (POME). (15th March 2020) - Ismail, Nur Farahein Hadina; Chai, Tan Meng; Daik, Rusli; Othaman, Rizafizah
ABSTRACT: Epoxidised natural rubber (ENR)/polyvinyl chloride (PVC)/silica (SiO2 ) membranes at a mass ratio of ENR and PVC 60:40 (%w/w) have been prepared by adding different silica amounts. The morphology, mechanical properties, water absorption capacity and water permeability of the membrane were investigated. The membranes were applied for palm oil mill effluent (POME) treatment, while treated and untreated POME were characterised by BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand) and pH. Scanning Electron Microscope (SEM) micrographs showed that the surface of the membrane has pores and this indicates the significance of silica as pore former. The mechanical properties of the membrane also improved by the addition of silica. Tensile strength increased from 10.18 to 16.90 MPa when the silica content is increased from 5 wt-% to 15 wt-%. Analyses of COD and BOD showed a reduction of 44% and 38.3%, respectively, after POME being treated by the membrane.